Study on the Mechanical Property of High‐Performance Silicon Carbide Fiber. Issue 7 (22nd January 2022) - Guo, Weina; Gao, Yantao; Hu, Wenfeng; Wu, Xiangji; Zhou, Haijun
Abstract : The mechanical behavior of silicon carbide (SiC) fiber used in ceramic matrix composites is valuable to permit the prediction of composite behavior and tailoring of composite properties. Herein, single‐fiber tensile tests of different SiC fibers are carried out and Weibull analysis is implemented to characterize its tensile property. To better understand its mechanical behavior, the surface and tensile fracture morphology of different fibers are observed by scanning electron microscopy (SEM) and the fiber elemental composition along the radial distribution is qualitatively analyzed by energy dispersive spectrometer (EDS). Also, the crystallinity and crystallite size of the fiber are analyzed by X‐ray diffraction (XRD). The results show that the tensile strength of SiC fiber conforms to the Weibull distribution, and its mechanical property is influenced by the surface morphology, elemental composition, crystallinity, and crystallite size. Abstract : The tensile strength of two typical SiC fibers is examined by Weibull analysis and its interfering factors of tensile property is illustrated by microstructure characterization.